Are frequent attenders also heartsink patients? Ali so pogosti obiskovalci za zdravnika tudi težavni bolniki? - Kersnik, Janko; Kuralt, Marija (Acta Medico-Biotechnica, 2021)
Purpose: Frequent attenders were often labelled as “heartsink patients”, who produce feelings of stress in their general practitioners (GPs). Our aim was to determine how often GPs label frequent attenders as difficult patients and to outline the characteristics of frequent attenders. Methods: We performed a cross sectional survey in general practice in Kranj, Slovenia. We draw a random sample of 100 frequent attenders and 300 non-frequent attenders aged 18 to 95 years from the GP list. Their GP have them a heartsink rating: very nice, nice, difficult, very difficult. We developed a regression prediction model for heartsink patients. Results: Frequent attenders were more likely patients labelled by a GP as nice or very nice patients. They were more likely to be older; to live with their families; to be retired; to have chronic disease, cancer, an injury or acute disease during the study year; and to need administrative services such as sickness leave certificates or repeat prescriptions. Regression analysis showed that older age, alcohol abuse, a higher number of visits in the year before the study year, and not being a frequent attender in the study year predicted assignment to the difficult patient group made by the GP. Conclusion: Heartsink patients are not a simple subgroup of frequent attenders. Nor is the ability to induce heartsink a characteristic of frequent attenders. The characteristics of heartsink patients should be further examined to help GPs surmount the job stress caused by them.